Bridging faith and reason: examining sertu concerns through Islamic and scientific lenses - Ahmad Fadzillah, Nurrulhidayah; Elgharbawy, Amal A M; Ahmad, Anis Najiha; Jamaludin, Mohammad Aizat; Minhat, Ade Erawan; Mohd Sukri, Siti Jamilah; A. A., Amira Safiah; Muhammad, Nurul Widad Fitri (Tazkia Islamic University College, 2024)
The examination of "sertu," a significant purification practice within Islam, from both Islamic and scientific angles, underscores its importance, especially in scenarios where water availability is limited. It entails purifying objects tainted by dog and pig waste. This investigation delves into sertu from Islamic and scientific perspectives, scrutinizing issues and distinguishing between sertu and samak. To fulfill the specified objectives, this research scrutinized scientific and Islamic literature sourced from academic journals, Dewan Bahasa Pustaka, and pertinent Malaysian guidelines for data collection. Furthermore, it analyzed the viewpoints of scholars representing major schools of thought such as Malikites, Shafiites, Hanbalites, and Hanafites. The researchers noted a dearth of scientific perspectives compared to Islamic ones. Additionally, a differentiation between sertu and samak arises, where samak pertains to the cleansing of animal skin using sharp instruments for specific purposes. The study concludes by advocating for further exploration to expand the discourse surrounding sertu from scientific standpoints.